Optimum Conditions for EOR Using Nanofluids Subjected to EM Waves - Muhammad Kashif; Poppy Puspitasari (Journal of Mechanical Engineering Science and Technology (JMEST), 2017)
Today‟s major challenge for oil industry is to improve the oil recovery from the reservoir. Various enhanced oil recovery (EOR) methods have been applied in the field and the steam injection is one of the most favourable methods. The deep reservoir will result in failure of this method due to excessive heat dissipation. In this situation, generating and injecting steam may be uneconomical due to the tremendous reduction of the recovery. Some methods using nanotechnology have been introduced and elaborated. However, we propose the electromagnetic (EM) method as an alternative due to its long range transmission of the transverse waves. These EM waves, coupled with some nanoparticles (NP), can modify the surface energy. We propose an optimum conditions based on some parameters namely, frequency, flux density, space charge density and skin depth, employing Maxwell and Helmholtz equations which interact with some magnetic and dielectric nanoparticles. A newly-designed EM antenna with a very high flux density is the model for this specific purpose. The electrical energy from the antenna transfers the waves to the dielectric and resistive nanoparticles, which is then transferred to the fluid with high capillary force. This results in lower surface tension which reduces the oil viscosity. In order to investigate the transport phenomena of the nanoparticles in porous medium, we applied Darcy‟s law. Our preliminary study for scale model simulations showed that at a frequency of 0.125Hz, the electric field of the curve antenna with magnetic feeders was 4280% higher compared to the one without magnetic feeders,At a frequency of 0.125Hz, the magnetic field of the curve antenna with magnetic feeders was 3677% higher in comparison with the one without magnetic feeders. With the increasing frequency from 0.125Hz to 9Hz, the electric field and magnetic field of the antenna with feeders decreased by 99%. The permeability and porosity of glass beads packed column was 30.58mD and 25.87% respectively. It was observed that the cumulative recovery of oil reached 21.11% by using ZnO nanofluid with electromagnetic waves, 17.23% by using ZnO nanofluid without electromagnetic waves, 32.59% by using iron oxide nanofluid with electromagnetic waves, and 29.68% by using iron oxide nanofluid without electromagnetic waves. In summary, the use of ZnO and iron oxide nanoparticles as nanofluids with electromagnetic waves is considered the most effective to use in enhanced oil recovery.